Influence of Perceived Organizational Support and Work Engagement on the Contextual Performance of Entrepreneurs - Satria Efandi; Riva Nadia Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of perceived organizational support and work engagement on the contextual performance of entrepreneurs in Padang City. Contextual performance is an important aspect of the work environment, reflecting the voluntary behavior of employees or entrepreneurs in helping, collaborating, and supporting organizational or business goals beyond their core duties. In the context of entrepreneurship, contextual performance can influence business continuity and development, as highly committed entrepreneurs tend to demonstrate greater initiative, loyalty, and involvement in business processes. Perceived organizational support, the extent to which individuals feel valued and supported by the organizational environment or business community, is a determining factor in shaping these positive behaviors. Meanwhile, work engagement reflects the level of enthusiasm and dedication of individuals in carrying out their business roles. This study used a quantitative approach with a cross-sectional method, and data were collected through a survey of 1,146 entrepreneurs in Padang City, West Sumatra Province. The analysis showed that both perceived organizational support and work engagement significantly influenced the contextual performance of entrepreneurs. The coefficient of determination (R²) of 0.67 indicates that 67% of the variation in contextual performance can be explained by these two variables (p < 0.01). This finding underscores the importance of creating a supportive environment and encouraging high work engagement in the entrepreneurial context. Therefore, business owners, policymakers, and business community managers need to consider these two factors when designing comprehensive business performance improvement strategies to support regional economic growth.